Changes in Plasma Levels of Protease and Fibrinolytic Inhibitors Induced by Treatment in Acute Myeloid Leukemia - Velasco, F; Torres, A; Andres, P; Martinez, F; Gomez, P (Thrombosis and Haemostasis, 1984)
We have studied the main protease inhibitors of leukocytes, alpha-1-protease (α1-PI), alpha- 1-antichymotrypsin (α1-Achy) and alpha-2-macroglobulin (α2-M), as well as different parameters of coagulation and fibrinolysis in 21 cases of acute nonlymphoblastic leukemia (ANLL) before, during and after therapy.Nine of the patients presented signs of DIC, 8 of whom belonged to subtype M3 and to subtype 1 M1.The initial α1-PI and α1-Achy levels, which were elevated, increased during the treatment period. There was no significant difference between patients with and without DIC. However, those leukemic patients with DIC showed a significant decrease in plasminogen (p <0.005) and fast antiplasmin (p <0.01) only during the treatment compared with DIC free patients. All DIC cases demonstrated circulating plasmin-antiplasmin complex (P-AP) both before and during treatment.Independent of a possible proteolytic action of leukocyte enzymes on clotting factors in the clinical course of ANLL (mainly M3 subtype), our results suggest an activation of plasminmediated fibrinolysis related to the activation of plasminogen by leukocytes, reactive DIC or both.
Keywords: Leukocyte proteases; ANLL; DIC; Fibrinolytic inhibitors; P-AP complex